Oral Inosine Persistently Elevates Plasma antioxidant capacity in Parkinson's disease. Issue 3 (25th January 2016) - Bhattacharyya, Shamik; Bakshi, Rachit; Logan, Robert; Ascherio, Alberto; Macklin, Eric A.; Schwarzschild, Michael A.
ABSTRACT: Introduction: Higher serum urate predicts slower progression in PD. The aim of this work was to assess whether oral inosine alters antioxidant capacity of plasma or CSF or urinary markers of oxidative injury in early PD. Methods: We assayed plasma and CSF antioxidant capacity by ferric‐reducing antioxidant power and measured DNA oxidation adduct 8‐hydroxydeoxyguanosine from urine in Safety of URate Elevation in PD, a randomized, placebo‐controlled trial of oral inosine assessing safety of elevating serum urate from <6 mg/dL to 6.1–7.0 or 7.1–8.0 mg/dL in patients with early PD. Results: At 6 months, antioxidant capacity was 29% higher among mild and 43% higher among moderate group participants compared to placebo and correlated with change in serum urate ( r = 0.86) and inversely with rate of clinical decline ( r = −0.26). CSF antioxidant capacity and urine 8‐hydroxydeoxyguanosine did not differ. Conclusions: The findings demonstrate a dose‐dependent, persistent elevation of plasma antioxidant capacity from oral inosine of potential therapeutic relevance. © 2016 International Parkinson and Movement Disorder Society